The extent and determinants of production efficiency of farmers in the rainforest margins in Central Sulawesi, Indonesia: Implications for land use and support services - Alene, D.; Zeller, M.; Schwarze, S.; Nuryartono, N. (2005)
There has been widespread concern regarding agricultural land expansion through deforestation, and a number of policy options have been proposed to counteract this trend. However, little effort has been made to assess the role of more efficient use of existing agricultural land and technology in combating deforestation. This study uses a translogstochastic frontier production function to analyze the technical efficiency of a sample of fanners in the rainforest margins in Indonesia. The sample farmers have an average technical efficiency of 53%, suggesting that there is a considerable potential for increasing production through efficient use of existing agricultural land and available technology. An analysis of socio-economic and institutional factors revealed that education, extension services, and social capital have a positive and significant influence on the fanners' performance.